Definiteness and Maximality in French Language Acquisition, More Adult-Like Than You Would Expect - Royle, Phaedra; Fromont, Lauren A.; Drury, John E. (Frontiers in Communication, 2018)
This study considers the mastery of maximality, or domain restrictions, in a group of 47 children acquiring French (aged 4;06 to 8;09), as well as a control group of young adults. Definite (le ‘the’) and indefinite (un ‘a/one’) singular and plural (des ‘some’, les ‘the’) as well as explicitly maximal contexts (tous les ‘all the’) were provided to participants. Animals were arranged in groups of three. Participants were asked to select one or more animals from these groups and give them to the experimenter (similar to Munn et al., 2006). Following Munn, we expected children to make maximality errors on the singular definite items. However, we did not observe this pattern. On the contrary we observed more errors on plurals generally. Further, the developmental patterns show that participants become less maximal in their responses to indefinite plurals (an adult-like pattern, also found in Caponigro et al., 2012) with no important changes on definite types: no strong age effects are observed on maximality patterns. These point to the importance of cross-linguistic data for the understanding of child language acquisition and error patterns for psycholinguistic theory.